Design of Three-Section Current Protection Experimental Device for Single - Xiaodong Bao; Yongzhi Wang; Liang Jin (MATEC Web of Conferences, 2018)
Based on the design idea of microcomputer protection, a set of three-section current protection, experimental device was designed by using MCU. Using MCU as the core control of experimental device, the circuits were designed, including the passive filter, current acquisition and signal output; real-ti me, current data were collected. When the current exceeded the setting value, the three-section protection had the single hop or linkage, thereby sending out a tripping signalto the simulated circuit breaker. By testing, the device could store data such as real-time acquisition of the current, alarm, tripping and closing in local database and cloud database, and realize remote monitoring and analysis of devices through cloud service., The device basically reached the goal of laboratory experiment teaching.